Evaluation of the Magicplex™ Sepsis Real-Time Test for the Rapid Diagnosis of Bloodstream Infections in Adults - Zboromyrska, Yuliya; Cillóniz, Catia; Cobos-Trigueros, Nazaret; Almela, Manel; Hurtado, Juan Carlos; Vergara, Andrea; Mata, Caterina; Soriano, Alex; Mensa, Josep; Marco, Francesc; Vila, Jordi (Frontiers in Cellular and Infection Microbiology, 2019)
Sepsis is a serious health condition worldwide, affecting more than 30 million people globally each year. Blood culture (BC) is generally used to diagnose sepsis because of the low quantity of microbes occurring in the blood during such infections. However, approximately 50% of bloodstream infections (BSI) give negative BC, this figure being higher for sepsis, which delays the start of appropriate antimicrobial therapy. This prospective study evaluated a multiplex real-time polymerase chain reaction, the MagicplexTM Sepsis test (MP), for the detection of pathogens from whole blood, comparing it to routine BC. We analysed 809 blood samples from 636 adult patients, with 132/809 (16.3%) of the samples positive for one or more relevant microorganism according to BC and/or MP. The sensitivity and specificity of MP were 29% and 95%, respectively, while the level of agreement between BC and MP was 87%. The rate of contaminated samples was higher for BC (10%) than MP (4.8%) (P < 0.001). Patients with only MP-positive samples were more likely to be on antimicrobial treatment (47%) than those with only BC-positive samples (18%) (P = 0.002). In summary, the MP test could be useful in some clinical setting, such as among patients on antibiotic therapy. Nevertheless, a low sensitivity demonstrated impairs its use as a part of a routine diagnostic algorithm.